2016
DOI: 10.1186/s12874-016-0162-y
|View full text |Cite
|
Sign up to set email alerts
|

Cochrane plain language summaries are highly heterogeneous with low adherence to the standards

Abstract: BackgroundThe aim of this study was to analyze whether Cochrane plain language summaries (PLSs) adhere to the Standards for the reporting of Plain Language Summaries in new Cochrane Intervention Reviews (PLEACS).MethodsA systematic analysis of adherence to the measurable PLEACS items was performed for Cochrane PLSs published from March 2013 to the end of January 2015. Duplicate independent data extraction was performed. An adherence score was calculated for each PLS and for the Cochrane Review Groups (CRGs) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…This means that there should be a balance between reading ease and accurate information about health. Cochrane has been testing different interventions to this aim, including PLEACS standards (Plain Language Expectations for Authors of Cochrane Summaries) for writing plain language summaries [15]. However, the authors of Cochrane systematic reviews, who write both the Scientific abstract and the Plain language summary formats, often do not follow these standards [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that there should be a balance between reading ease and accurate information about health. Cochrane has been testing different interventions to this aim, including PLEACS standards (Plain Language Expectations for Authors of Cochrane Summaries) for writing plain language summaries [15]. However, the authors of Cochrane systematic reviews, who write both the Scientific abstract and the Plain language summary formats, often do not follow these standards [15].…”
Section: Discussionmentioning
confidence: 99%
“…Cochrane has been testing different interventions to this aim, including PLEACS standards (Plain Language Expectations for Authors of Cochrane Summaries) for writing plain language summaries [15]. However, the authors of Cochrane systematic reviews, who write both the Scientific abstract and the Plain language summary formats, often do not follow these standards [15]. Other formats, such as infographics, may also not be better for understanding the results of a Cochrane systematic review in comparison to a well-written plain language summary [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cochrane PLSs is an important knowledge translation tool of the Cochrane, as they present high‐quality evidence in non‐expert language. Even though Cochrane PLSs are not uniformly written, and sometimes they contain language that is not plain, they bring useful information about Cochrane review findings to individuals without medical education.…”
Section: Discussionmentioning
confidence: 99%
“…The aim is to "summarize the review in a straightforward style that can be understood by consumers of health care," says Nancy Owens, senior communication manager at Cochrane. Although authors are given guidelines to help them write a summary for their review, a recent study found that none of the plain-language summaries published by Cochrane during a 23-month period fully adhered to these guidelines ( Jelicic Kadic et al, 2016 ). Owens says that Cochrane is currently involved in a project to "to improve and standardize the content, presentation, and readability of plain-language summaries to make them easier to read, use, and translate into other languages."…”
Section: Who Reads Plain-language Summaries?mentioning
confidence: 99%